2014
DOI: 10.1016/j.bbadis.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of microRNAs in vascular damage in experimental chronic kidney disease

Abstract: Chronic kidney disease (CKD) is associated with vascular calcifications and atherosclerosis. There is a need for novel predictors to allow earlier diagnosis of these disorders, predict disease progression, and improve assessment of treatment response. We focused on microRNAs since they are implicated in a variety of cellular functions in cardiovascular pathology. We examined changes of microRNA expression in aortas of CKD and non-CKD wild type mice and apolipoprotein E knock-out mice, respectively. Both vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 39 publications
7
63
1
Order By: Relevance
“…miRNA levels have been associated with CKD in previous studies by our team and by other authors, in both cellular and animal models [810]. In a murine CKD model, we have shown that miR-126, miR-143, miR-145 and miR-223 are implicated in the vascular complications that occur during the later stages of CKD [9]. miR-126 is endothelial-specific and implicated in endothelial dysfunction [11].…”
Section: Introductionmentioning
confidence: 77%
“…miRNA levels have been associated with CKD in previous studies by our team and by other authors, in both cellular and animal models [810]. In a murine CKD model, we have shown that miR-126, miR-143, miR-145 and miR-223 are implicated in the vascular complications that occur during the later stages of CKD [9]. miR-126 is endothelial-specific and implicated in endothelial dysfunction [11].…”
Section: Introductionmentioning
confidence: 77%
“…We examined a series of miRs implicated in kidney cell apoptosis and angiogenesis. [19][20][21] Unlike the involvements of miR-21, miR-27, miR-126, and miR-192 in other forms of kidney disease, 22,23 we found no change in the expression of these miRs in RVD, possibly because of different disease and species settings. For example, miR-21 contributes to xenon-conferred amelioration of renal ischemia-reperfusion injury in mice 24 but plays a pathogenic role in kidney fibrosis in mice with unilateral ureteral obstruction.…”
Section: Discussioncontrasting
confidence: 65%
“…[44]. Although no study has yet measured miR-135a expression in this population, some studies have revealed the involvement of miRs in vascular damage in experimental chronic kidney disease [45], such as miR-126, -143 and -223. As miR-135a plays an important role in vascular calcification, the relationship between it and the chronic kidney disease requires further study.…”
Section: Discussionmentioning
confidence: 99%